Methylglyoxal Scavengers Resensitize KRAS-Mutated Colorectal Tumors to Cetuximab - Justine Bellier; Marie-Julie Nokin; Maurine Caprasse; Assia Tiamiou; Arnaud Blomme; Jean L. Scheijen; Benjamin Koopmansch; Gillian M. MacKay; Barbara Chiavarina; Brunella Costanza; Gilles Rademaker; Florence Durieux; et al. (Cell Reports, 2020)
Summary: The use of cetuximab anti-epidermal growth factor receptor (anti-EGFR) antibodies has opened the era of targeted and personalized therapy in colorectal cancer (CRC). Poor response rates have been unequivocally shown in mutant KRAS and are even observed in a majority of wild-type KRAS tumors. Therefore, patient selection based on mutational profiling remains problematic. We previously identified methylglyoxal (MGO), a by-product of glycolysis, as a metabolite promoting tumor growth and metastasis. Mutant KRAS cells under MGO stress show AKT-dependent survival when compared with wild-type KRAS isogenic CRC cells. MGO induces AKT activation through phosphatidylinositol 3-kinase (PI3K)/mammalian target of rapamycin 2 (mTORC2) and Hsp27 regulation. Importantly, the sole induction of MGO stress in sensitive wild-type KRAS cells renders them resistant to cetuximab. MGO scavengers inhibit AKT and resensitize KRAS-mutated CRC cells to cetuximab in vivo. This study establishes a link between MGO and AKT activation and pinpoints this oncometabolite as a potential target to tackle EGFR-targeted therapy resistance in CRC. : Bellier et al. demonstrate that MGO stress is a constant feature of KRAS-mutated CRC tumors. MGO induces a key survival pathway implicated in resistance to EGFR-targeted therapy in CRC. The scavenging of this oncometabolite could be beneficial in the treatment of both wild-type and mutant KRAS CRC tumors. Keywords: methylglyoxal, colorectal cancer, KRAS mutation, EGFR-targeted therapy, Hsp27, carnosine, aminoguanidine, cetuximab, AKT signaling